Antiviral activity of SAFER®, a commercial acidifying desiccant powder, against African swine fever virus - Trinh, Thi Bich Ngoc; Lazenec, Elodie; Lai, Thi Ngoc Ha; Matard-Mann, Maria; Phat, Luong Tan; Morvan, Anne; Delahaye, Anne-Cecile; Collén, Pi Nyvall; Nguyen, Thi Lan; Le, Van Phan (Frontiers in Veterinary Science, 2024)
African swine fever (ASF) is one of the deadliest swine diseases, causing significant economic losses, threatening food security, and limiting pig production in affected countries. In the absence of an effective ASF vaccine, prevention and control of ASF depend mainly on effective biosecurity measures. In this study, the efficacy of SAFER®, a powdered disinfectant containing clay, an acid complex, and the active ingredient thyme essential oil, was tested against the ASF virus. The results showed that ASFV isolate (VNUA/HY/ASF1/Vietnam/2019) was inactivated by 3.5 and 5 Log10HAD50/ml after 20 and 120 min of treatment with SAFER®, respectively. When body fluids contaminated with ASFV, such as blood, saliva, urine, and feces, were treated with SAFER® for 20 min, the ASFV titer was reduced by 1.6, 2.2, 2.0, and 2.2 Log10HAD50/ml, respectively.